2023
DOI: 10.3389/fnagi.2023.1142163
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anoikis-related genes classification patterns and immune infiltration characterization in ischemic stroke based on machine learning

Abstract: IntroductionIschemic stroke (IS) is a type of stroke that leads to high mortality and disability. Anoikis is a form of programmed cell death. When cells detach from the correct extracellular matrix, anoikis disrupts integrin junctions, thus preventing abnormal proliferating cells from growing or attaching to an inappropriate matrix. Although there is growing evidence that anoikis regulates the immune response, which makes a great contribution to the development of IS, the role of anoikis in the pathogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…“ClusterProfiler,” “enrichplot,” and “org.Hs.eg.db” packages were used to analyze important functions and pathways of DEGs, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) ( Qin et al, 2023 ). The reference genome file “c2.cp.kegg.Hs.symbols.gmt” was used for gene set enrichment analysis (GSEA) to understand the differences in pathways between control and experimental groups ( Qin et al, 2023 ). All results were visualized by the “ggplot2” software package.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…“ClusterProfiler,” “enrichplot,” and “org.Hs.eg.db” packages were used to analyze important functions and pathways of DEGs, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) ( Qin et al, 2023 ). The reference genome file “c2.cp.kegg.Hs.symbols.gmt” was used for gene set enrichment analysis (GSEA) to understand the differences in pathways between control and experimental groups ( Qin et al, 2023 ). All results were visualized by the “ggplot2” software package.…”
Section: Methodsmentioning
confidence: 99%
“…We use the LASSO, SVM-RFE and RF algorithms ( Qin et al, 2023 ) to screen key genes in the above functional modules. The feature genes were first screened using the LASSO algorithm to obtain a “LASSO coefficient path” and a “LASSO regularization path” (also known as Lasso regression analysis cross-validation curve).…”
Section: Methodsmentioning
confidence: 99%
“… 12 Its primary role is to prevent abnormal cell growth and adhesion to an abnormal extracellular matrix. 13 Anoikis is crucial for tissue homeostasis and development and is involved in the regulation of diseases, such as metastatic cancer, cardiovascular disease, and diabetes. 14 Dobler reported that endothelial cells undergo shedding and anoikis in high glucose environments.…”
Section: Introductionmentioning
confidence: 99%
“…Using machine learning to search for differentially expressed genes in IS patient data set has drowned great interest. Qin et al [21] investigated the role of anoikisrelated genes (ARGs) in IS, which employed machine learning to classify IS samples, identified key ARGs, and constructed diagnostic models. Ren et al [22] discovered inflammation-related biomarkers for IS using machine learning.…”
Section: Introductionmentioning
confidence: 99%